Topological Ordering and Viscosity in the Glass-Forming Ge–Se System: The Search for a Structural or Dynamical Signature of the Intermediate Phase - Zeidler, Anita; Salmon, Philip S.; Whittaker, Dean A. J.; Pizzey, Keiron J.; Hannon, Alex C. (Frontiers in Materials, 2017)
The topological ordering of the network structure in vitreous GexSe1−x was investigated across most of the glass-forming region (0 ≤ x ≤ 0.4) by using high-resolution neutron diffraction to measure the Bhatia-Thornton number-number partial structure factor. This approach gives access to the composition dependence of the mean coordination number n¯ and correlation lengths associated with the network ordering. The thermal properties of the samples were also measured by using temperature-modulated differential scanning calorimetry. The results do not point to a structural origin of the so-called intermediate phase, which in our work is indicated for the composition range 0.175(8) ≤ x ≤ 0.235(8) by a vanishingly small non-reversing enthalpy near the glass transition. The midpoint of this range coincides with the mean-field expectation of a floppy-to-rigid transition at x = 0.20. The composition dependence of the liquid viscosity, as taken from the literature, was also investigated to look for a dynamical origin of the intermediate phase, using the Mauro-Yue-Ellison-Gupta-Allan (MYEGA) model to estimate the viscosity at the liquidus temperature. The evidence points to a maximum in the viscosity at the liquidus temperature, and a minimum in the fragility index, for the range 0.20 ≤ x ≤ 0.22. The utility of the intermediate phase as a predictor of the material properties in network glass-forming systems is discussed.